ANALISIS STRATEGI GURU IPS DALAM MENGELOLA KELAS UNTUK MEMOTIVASI BELAJAR SISWA - Mohammad Fitri; Aprilia Imelda; M. Taufik Arifin (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
This study aims to describe the social studies teacher's strategy in managing the classroom to motivate student learning. This research was conducted in junior high school. The research method used is a qualitative method. Data was collected by means of documentation, interviews, and observation techniques. Data analysis was carried out in several stages, namely, collecting data, reducing data, presenting data, and concluding. The results of the study are: first, the teacher's strategy in managing the classroom is related to the preparation of learning tools, the preparation of the classroom, and the psychological preparation of students. Second, there are factors that hinder classroom management, namely the lack of handbooks and teaching aids, as well as the decreased level of student learning motivation caused by facilities and rooms that do not support the learning process.